2016
DOI: 10.1038/srep24038
|View full text |Cite
|
Sign up to set email alerts
|

Direct Copolymerization of CO2 and Diols

Abstract: Direct polymerization of CO2 and diols is promising as a simple and environmental-benign method in place of conventional processes using high-cost and/or hazardous reagents such as phosgene, carbon monoxide and epoxides, however, there are no reports on the direct method due to the inertness of CO2 and severe equilibrium limitation of the reaction. Herein, we firstly substantiate the direct copolymerization of CO2 and diols using CeO2 catalyst and 2-cyanopyridine promotor, providing the alternating cooligomers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 77 publications
(81 reference statements)
2
70
0
Order By: Relevance
“…In addition, picolinate‐capped cooligomers were also observed, which may be a cause for the low molecular weight. This method is also applicable to various diols including linear C4–C10 α,ω‐diols to give high yields of the corresponding cooligomers (Table ), which cannot be obtained by well‐known methods such as copolymerization of CO 2 and cyclic ethers and ring‐opening polymerization of cyclic carbonates.…”
Section: Synthesis Of Organic Carbonates From Co2+alcohols Over Ceo2 mentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, picolinate‐capped cooligomers were also observed, which may be a cause for the low molecular weight. This method is also applicable to various diols including linear C4–C10 α,ω‐diols to give high yields of the corresponding cooligomers (Table ), which cannot be obtained by well‐known methods such as copolymerization of CO 2 and cyclic ethers and ring‐opening polymerization of cyclic carbonates.…”
Section: Synthesis Of Organic Carbonates From Co2+alcohols Over Ceo2 mentioning
confidence: 93%
“…Another interesting profile of the results of CO 2 +1,3‐propanediol+2‐cyanopyridine is the reaction time dependence (Figure ), where the experimental method was similar to that in our previous report on the synthesis of polycarbonate from CO 2 +diols+2‐cyanopyridine . At short reaction time, the selectivity of cyclic trimethylene carbonate was high, however, it decreased with increasing the reaction time.…”
Section: Synthesis Of Organic Carbonates From Co2+alcohols Over Ceo2 mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, development of catalyst systems which can sophisticatedly control the reactivities of the three components and overcome the equilibrium limitation is desirable. Recently, we found that combination of CeO 2 and 2‐cyanopyridine was an effective catalyst system for the synthesis of dimethyl carbonate (DMC) from CO 2 +CH 3 OH and cyclic carbonates and polycarbonates from CO 2 +diols. Urakawa and co‐workers also applied the combination catalyst system to the DMC synthesis at high CO 2 pressure .…”
Section: Methodsmentioning
confidence: 99%
“…At present the ring‐opening polymerization of six‐membered cyclic carbonate monomers, commonly derivatives of trimethylene carbonate (TMC, IUPAC: 1,3‐dioxan‐2‐on) and the polycondensation of dialkyl carbonates with diols are the established pathways for the synthesis of functional aliphatic polycarbonate (PCs) . Furthermore, the direct polymerization of CO 2 and diols was described in the literature . For the synthesis of poly(trimethylene carbonate) (PTMC) and poly(dimethyl trimethylene carbonate) functional polymer analogs, cyclic carbonates bearing a variety of functional groups have been developed ( Figure ) .…”
Section: Introductionmentioning
confidence: 99%